Yield Response of Hybrid and Open Pollinated Maize (Zea mays L.) Varieties to Different Levels of Fertilizer Nitrogen under Rain-Fed Conditions in the Bono Region of Ghana - Eric Ansu; Kwadwo Gyasi Santo; Abdul Aziz Khalid; Muntala Abdulai; Daniel Ntiamoah Afreh; Kwabena Atakora (International Journal of Agronomy)
Background. The experiment was undertaken at Nsapor, a suburb of Berekum municipality in the Bono Region of Ghana, from March 2019 to November 2019 to determine the suitable rate of fertilizer nitrogen application to optimize seed yield and yield attributes of Pannar 12 and Omankwa maize varieties in a semi deciduous agroecology of Ghana. Soil fertility is low in Ghana because of factors such as rampant annual bushfires, short fallow periods as a result of high human populations, continuous cropping, deforestation, and improper mining activities. There is also little information on crop variety and site-specific fertilizer recommendations in Ghana, resulting in inappropriate use of fertilizers by most Ghanaian farmers, culminating in low crop yields. Methods. Hybrid (Pannar 12) and open pollinated (Omankwa) maize varieties were treated with four rates of fertilizer nitrogen obtained from NPK 15-15-15 (0 kgN/ha, 90 kgN/ha, 120 kgN/ha and 150 kgN/ha) and laid out in a factorial combination in a randomized complete block design with three replicates. Results. Application of 150 kg/ha of fertilizer N to Pannar 12 variety resulted in grain yields of 6146 kg/ha and 6095 kg/ha in the major and minor rainy seasons, respectively. The results also showed that application of 120 kg/ha of fertilizer N to Omankwa variety gave grain yields of 4635 kg/ha and 5286 kg/ha in the major and minor rainy seasons, respectively. To optimize the grain yield of maize, farmers could use NPK 15-15-15 fertilizer as a source of nitrogen and apply 120 kgN/ha to Omankwa variety and 150 kgN/ha to Pannar 12 variety in both major and minor rainy seasons.